Environmental and Health Services Factors Associated with New Covid19 Case in Central Java Province: A Spatial Analysis - Sidiq Purwoko; Yeny Yulistanti; Diyan Ermawan Effendy; Afi Nursafingi; Ina Kusrini (Universitas Airlangga, 2023)
Introduction: At the end of December 2020, there were 93,035 Covid19 cases reported in Central Java. The spatial analysis is useful for assessing the association of environmental and health services factors with new Covid19 cases. Methods: This study was conducted to identify a spatial autocorrelation between environmental conditions and health services on new Covid19 cases in Central Java Province in 2020. The data were obtained from Central Java Profile Published in 2021 with a cross-sectional design. This autocorrelation regression technique was used to determine the relationship between districts/cities for new Covid19 cases. The independent variables in this study were environmental factors such as access to quality drinking water, access to quality sanitation, percentage of Open Defecation Free (ODF) villages, and percentage of healthy food management places. In addition, the independent variables also covered health service factors such as the number of public health centers, hospitals, medical personnel, and population density. Results and Discussion: The findings found that in Central Java province, the factors that influenced new Covid19 cases included population density (p-value 0.0001; Morran I -0.032) and the number of medical personnel (p-value 0.0001; Morrans I 0.021). Conclusion: The new cases of Covid19 in Central Java Province formed a clustered pattern. Factors significantly influencing the regression test are population density and the number of medical personnel. Besides that, spatial autocorrelation was also found in other variables in this study but was not significant.